AIR EMBOLISM DEVELOPED AS A RESULT OF OPENING THE CENTRAL CATHETER TIP BY THE PATIENT'S RELATIVE - Yildirim, Fatma; Karaman, Irem; Yetkin, Emir; Poyraz, Umur; Şimşek, Meltem (Journal of Ayub Medical College Abbottabad, 2022)
Central catheterization can be placed in critically ill patients in the intensive care unit (ICU) for some purposes such as dialysis, nutrition, and hemodynamic monitoring. Air embolism is a very rare complication of central catheterization. A 46-year-old male patient with no known comorbidities underwent laparoscopic total colectomy and protective loop ileostomy for colon cancer. He was taken to the general surgery ICU for close hemodynamic follow-up in the postoperative period. Since he was cachectic and could not reach the target of oral nutrition within 1 week, a central catheter was inserted in the right internal jugular vein with ultrasonographic imaging, and total parenteral nutrition (TPN) was started. The patient, who had no additional problems in the follow-up, was transferred to the general surgery ward. Three and half hours after the transfer, the patient became unconscious and had extensor posture. Therefore, emergency cranial computed tomography (CT) was performed and he was taken back to the ICU. There was no finding in favour of bleeding in cranial CT. The patient was intubated to protect the airway, as he had a generalized tonic-clonic seizure during his follow-up. Air bubbles were seen in the main pulmonary artery and right ventricle in the multidetector thorax CT. Cranial CT angiography was taken at the 24th hour, and diffusion cranial MRI was performed for diagnosis of central air embolism. No air was detected to be aspirated in the cerebral arteries in cranial CT angiography. On the 6th day, the patient regained consciousness, extubated, and physical therapy was started. On the 12th day of hospitalization, the patient was discharged with 2/5 loss of motor power in the left upper extremity. When the patient's wife's anamnesis was detailed, it was learned that in order to mobilize the patient, she separated the TPN from the catheter and left the catheter tip open.